DEVELOPING A SCIENCE PROGRAM FOR RAPID LEARNERS. - Passow, A. Harry (Science Education, 1957)
The article focuses on the aspects to consider to develop a science program for rapid learners. The program should result in basic understanding and meaning which constitute science in general education. Its emphasis is not limited to information alone. Moreover, it must be able to stimulate intellectual attainment and scholarship for students. The science program must provide the special skills, knowledge and attitudes needed by those students who are potential scientists. It must serve both general and special education function.